ANALYSIS MODEL AND FINANCIAL RISK MITIGATION STRATEGY IN DECISION MAKING FOR THE FEASIBILITY OF INVESTMENT IN THE DEVELOPMENT OF HYDROPELECTRIC POWER PLANT (PLTA) IN THE NORTH SUMATRA REGION - Anindityo Aryo Saloko; Isfenti Sadalia; Nazaruddin (PT. Radja Intercontinental Publishing, 2024)
The isuccess iof iimplementing ia iconstruction iproject ican ibe iseen ifrom ithe iaccuracy iin imaintaining itriple iconstraints i(cost, iquality iand itime). iProject irisk ianalysis ifor ilong-term iinvestment iand isuccessful iproject idevelopment iplanning iis ivery iimportant, imodel ianalysis iis ineeded ito imitigate irisk idue ito ithe icomplexity iof ithe iproblems ifaced iin ithe idevelopment iof ipower iprojects, iespecially ipower iplants iin iNorth iSumatra iProvince iwith ithe idevelopment iof ihydroelectric ipower iprojects i(PLTA). iThere iare irisk ievents ithat icould ihamper ithe ismooth idevelopment iof ithe i45 iMW ihydropower iplant iconstruction iproject iin ithe iNorth iSumatra iregion iwith ian iemphasis ion iinvestment ifinancial irisks. iThe ifollowing iare irisk ievents ithat iwere iidentified iand ithen iafter imeasurement iand ianalysis, irisk ipriorities iwere iobtained ithat imust ibe imanaged ifirst, iincluding: iproject ifinancing igovernance, icash iflow imanagement, idetailed icontract ispecifications, iand idifficulties iin ifulfilling imaterials. iThese irisk ievents iare imanaged iby iinterpreting ithem iin ithe imanagement iof irisk imitigation iagainst ifinancial ilosses iin ithe iimplementation iof ithe iconstruction iof ia i45 iMW ihydroelectric ipower iplant iin ithe iNorth iSumatra iregion. iThe iresults iof ithe irisk imitigation ianalysis ishowed ithat iProject iFinancing iManagement iwas ithe ifirst irisk ipriority, ithen iProject iCash iFlow iManagement iwas ithe isecond ipriority, iDetailed iContract iSpecifications iwere ithe ithird ipriority, iand iDifficulty iFulfilling iMaterials iwas ithe ifourth ipriority. iImplementation iof iresearch ifindings, inamely iprioritization iof irisk ireduction, irequires iidentifying icritical iprocesses iand iimmediately iadopting iapproaches ito iprovide ialternative icontrols ifor iidentified icritical iprocesses. iFor iexample, iif ithe itotal icost iapproach iis ia icritical iprocess, ithen iprocurement iof ihydroelectric iplant imaterials iis iconsidered ia icritical iprocess. iAn iexploratory iapproach ican ibe iused ito imanage icritical iprocesses, inamely iby imaking icontracts iwith imaterial isuppliers iso ithat imaterials iare iordered iin iadvance i(with ior iwithout ia idown ipayment) ito iarrive iaccording ito ithe iproject ischedule. iFor iother icritical iprocesses iidentified iusing iother iapproaches, iyou ican iuse ithe iresults iof irisk imitigation iprioritization ibased ion irisk ievents. iThe iapplication iof ithis imitigation ican ibe icarried iout iflexibly iaccording ito ifurther iidentification iobtained.